Building Confidence in Information−Trustworthiness Metrics for Decision Support - Nurse, J; Agrafiotis, I; Creese, S; Goldsmith, M; Lamberts, K (IEEE, 2013)
In light of the significant amount of information available online today and its potential application to a range of situations, the importance of identifying trustworthy information, and secondly, of building user confidence in that information is paramount. With this in mind, we have developed a novel trustworthiness metric which is designed to provide a relative score based on several key factors that influence trust, such as information's provenance and quality, and the integrity of the infrastructure through which the information passes. In this paper we consider whether providing insight into the various factors that make-up the resulting trustworthiness score actually helps to build trust in the metric itself, and whether users can successfully understand the advice being conveyed. Specifically, we present here the results of experiments which explore whether or not the visual interface that enables users to understand how the metric is composed of a combination of scores, across a range of factors, is a feature they are cognitively able to process, and whether it might help to build confidence in the trustworthiness advice being provided.